Fauna of the Western Ghats and Their Protection: Exploring the biodiversity and conservation challenges of the Western Ghats (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Western Ghats are a chain of hills that run along the western edge of peninsular India. Their proximity to the ocean and through orographic effect, they receive high rainfall. These regions have moist deciduous forest and rain forest. The Western Ghats, known locally as the Sahyadri Hills. They cover an area of about 160,000 km² and stretch for 1,600 kilometers from the country's southern tip to Gujarat in the north, interrupted only by the 30 kilometers Palghat Gap. The region shows high species diversity as well as high levels of endemism. Nearly 77 of the amphibians and 62 of the reptile species found here are found nowhere else. Western Ghats are one of the major biodiversity hotspots in the world. The purpose of biodiversity hotspots is not simply to identify regions that are of high biodiversity value, but to prioritize conservation spending. The Western Ghats mediates the rainfall regime of peninsular India by intercepting the southwestern monsoon winds. There are four main reasons for the loss of biodiversity vz., 1. Habitat destruction 2. Resource mismanagement 3. Poaching 4. Climate change. Conservation efforts are on through protected areas.